The Role of Soundscape on Urban Attractiveness in Traditional Cities - Basil, Tiba; Abed Hassan, Susan (Technium Sustainability, 2024)
The soundscape is an immanent part of the open spaces in historical cities. This study aims to investigate the role of soundscape in enhancing urban attraction and its effect on intentional behavior. This is based on a questionnaire survey, which is conducted in compliance with ISO/TS 12913-2:2018, of 31 visitors in the Almutanabi and Almurad (alkadhmya) streets in historical blocks in Baghdad city. SPSS software is used to analyze the data. The results indicate that soundscape has a positive significance on urban attraction and the overall response to the sound source identification shows that the sound of human beings is dominant strongly while the sound of technology comes in second place and the sounds of nature are limited. In general, positive soundscape perception may contribute to the urban attraction of open spaces in historical cities.